Exploring Sagittarius A* in gamma-rays with Fermi LAT Telescope - Cafardo, Fabio Muffo (2021)
Sagittarius A*the supermassive black hole (SMBH) in the center of our galaxyhas been identified in most of the electromagnetic spectrum, from radio to X-rays. Diffuse gamma-ray emission has been observed around Sagittarius A* and a gamma-ray point source has been detected coinciding with the SMBH\'s position, although there is still no definitive association between the two. In this work, we have used ~11 years of Fermi Large Area Telescope (LAT) observations of the point source 4FGL J1745.6-2859 and performed a detailed analysis across four energy bands. Our goal is to elucidate the nature of the gamma-ray emission at the Galactic Center (GC) and whether it is associated with the SMBH. We find that the centroids of the emission approach Sagittarius A*\'s location as the energy increases and they are spatially associated with gas-rich regions in the GC. Assuming that the gamma-ray point source is located at the GC, we estimate a luminosity of 2.61 x 10E36 erg/s in the 100 MeV to 500 GeV energy range. This is consistent with Sagittarius A*\'s bolometric luminosity. Based on the point source properties, we ruled out several potential candidates for its nature and favor a cosmic ray origin accelerated byor in the vicinity ofthe SMBH. We also created light curves (LCs), with time bins as short as 15 days, in search of variability in the 4FGL J1745.6-2859 gamma-ray flux. In contrast with Sagittarius A*\'s flaring behavior in longer wavelengths, we detect that its gamma-ray flux distribution is compatible with a Gaussian, representative of a normal random process, hinting that the gamma-ray emission mechanism differs substantially from the low-energy regime. Finally, 4FGL J1745.6-2859\'s spectral energy distribution (SED) shows a pion-decay bump characteristic of gamma-ray hadronic emission. Its SED is also compatible with several hadronic models for Sagittarius A*\'s gamma-ray emission. Our results indicate that the point source at the GC is indeed the gamma-ray counterpart of Sagittarius A* in the GeV range. The characteristics of this emissionits spatial coincidence with gas reservoirs, energetics, lack of variability and SEDsuggest that hadronic processes are likely behind its origin.